Permasalahan dan Solusi dalam MEnghapal al-Qur'an - Yulmiati Yumiati; Basri Mahmud; Muh. Fahran (Jurnal Ilmiah Tarbiyah Umat, 2024)
The problems studied in this research are: (1) What are the problems of students in memorizing the Qur'an at the Tahfidz Darussaqof Wonomulyo House, Polewali Mandar Regency, (2) What are the solutions for memorizing the Qur'an at the Tahfidz Darussaqof Wonomulyo House, Polewali Mandar Regency? This type of research is qualitative research that builds meaning based on field data. Data collection was carried out by conducting observations, in-depth interviews and documentation. Data analysis is carried out by giving meaning to the data that has been collected, and conclusions are drawn from this data. The results of observations from the problems of students in memorizing the Qur'an at the Tahfidz Darussaqof Wonomulyo House, Wonomulyo District, Polewali Mandar Regency are in the form of solutions found such as holding moral recitations, orderly administration, going for recreation or Rihlah, istiqomah in memorizing the Qur'an, forming whatsapp groups, adding teachers or ustads, implementing the Tazmi system and the Daras system 41 Times in teaching students to memorize the Qur’an. Keywords: Problems, solutions to memorizing the Qur’an